Leverage Ratio, Capital Intensity, and Inventory Turnover: Their Influence on the Effective Tax Rate of Textile and Garment Manufacturing Companies (2017–2023) - Aditya Wahyu Prabowo; Khoirul Rozikin; Elmiwati Elmiwati (International Journal of Economics and Management Research, 2025)
This study aims to evaluate the impact of debt ratios, capital intensity, and inventory turnover on effective tax rates (ETR) in manufacturing companies in the textile and garment sectors listed on the Indonesia Stock Exchange (IDX) during the 2017–2023 period. The background of this research stems from the urgency of fiscal efficiency to enhance the competitiveness of Indonesia's textile industry, which faces significant challenges from global economic pressures, fluctuating export demands, and increasing production costs. These external factors have pushed companies to seek strategic ways to manage their tax burden without violating prevailing regulations. The research adopts a quantitative approach, employing the Common Effect Model (CEM) in panel data regression, with data derived from 112 firm-year observations across 16 companies selected based on specific criteria. This approach is chosen for its effectiveness in analyzing the influence of multiple variables over time while controlling for company-specific characteristics. The empirical findings reveal that leverage, or debt ratio, does not significantly affect the ETR, suggesting that the use of debt as a tax shield is not effectively utilized or is neutralized by other factors such as regulatory constraints or conservative financial policies. In contrast, capital intensity—measured by the proportion of fixed assets—has a significant negative impact on ETR. This indicates that companies with higher investments in fixed assets can reduce their taxable income through depreciation expenses, making capital intensity a valuable tax planning tool. Meanwhile, inventory turnover shows a significant positive relationship with ETR. Although high inventory turnover generally indicates operational efficiency and strong sales performance, it may also lead to higher taxable income, thus increasing the overall tax burden. This paradox underlines the complexity of aligning operational efficiency with fiscal efficiency in practice.